Economics and Nature: A Long-Neglected Combination - Anna Pettini (Center for Economic Studies and ifo Institute (CESifo), 2023)
The intersection of Economics and Nature has long been overlooked, but recent events have shed new light on their interconnectedness. This paper explores this relationship, focusing on the impact of economic cycles and the role of GDP as a measure of economic success. The paper highlights the historically dominant role of GDP, tracing its origins from Simon Kuznets' report in the 1930s to the present. It considers the rise of quantitative growth as a paradigm and its influence on economic policy, including the neo-liberal perspective that prioritises private market initiative. The paper concludes by exploring the potential for change in the aftermath of the syndemic crisis, and argues for a move away from GDP-centred measurements towards indicators that are fully researched and ready to use.
Keywords: I31; O10; D00; 330; critical deceleration theory; nature; GDP; beyond-GDP indicators